2003
DOI: 10.1097/00003727-200310000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention Screening for Family Caregivers of Older Relatives in Primary Care Practices

Abstract: The Maine Primary Partners in Caregiving project provides a prime example of how disparate community health, social service, and higher education institutions can build a successful rural service alliance for the purposes of screening for family members experiencing stress during the provision of care to impaired older relatives. Community primary care practices are featured as prime sites for the early identification of elder caregivers experiencing stress and burden. Initial project results and implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…More work is needed to determine the need for and feasibility of screening for depressive symptoms in caregivers. Screening for caregiving and depressive symptoms has been undertaken in a rural primary care setting, 28 and the American Medical Association has developed a caregiver screening tool. 29 It was found that two simple questions were consistently correlated with membership in the highest depressive symptoms trajectory (lower life satisfaction and desire for more help from family and friends).…”
Section: Discussionmentioning
confidence: 99%
“…More work is needed to determine the need for and feasibility of screening for depressive symptoms in caregivers. Screening for caregiving and depressive symptoms has been undertaken in a rural primary care setting, 28 and the American Medical Association has developed a caregiver screening tool. 29 It was found that two simple questions were consistently correlated with membership in the highest depressive symptoms trajectory (lower life satisfaction and desire for more help from family and friends).…”
Section: Discussionmentioning
confidence: 99%
“…Since the caregiver role is often associated with physical and psychiatric diseases [ 10 , 56 ], it serves as a powerful predictor of greater risk for psychological distress, anxiety, depression and cardiovascular reactivity [ 12 , 56 , 57 ]. However, while the caregiving role can have a negative impact on caregivers, research has shown that the effects can be mitigated by assessing [ 58 ] and addressing caregiver needs [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outros autores identificaram diversos fatores de risco associados ao aumento do stresse físico e emocional do cuidador (Kaye, Turner, Butler, Downey, & Cotton, 2003):…”
Section: O Cuidador Informalunclassified